Pembaruan Kawasan Hutan untuk Mewujudkan Pembangunan Kehutanan yang Berkeadilan, Berkelanjutan, dan Berkedaulatan - Pungky Widiaryanto (Bappenas Working Papers, 2019)
After 70 years of Indonesia’s independence, the development of Indonesia’s forestry remains complex and complicated. Forests, that have contributed significant economic growth, nowadays are facing some challenges. Many issues come across, such as deforestation, forest concessions’ bankrupt, and land conflicts. Many experts claim that the underlying cause of these problems is related to the uncertainty of forest area and forest tenure. These problems do not only bring negative effects to society but also hinder other development agendas. Thus, Indonesia needs to reform its forest area and forest tenure. This idea is knowing as forest reform or agrarian reform or forest tenure reform. This article explains the facts of forest unfair tenure, the fact of forest cover in Indonesia, pros and cons about forest tenure reform, using strategic environmental assessment to evaluate forest tenure reform, and also proposal policy framework. Currently, the government is preparing the mid-term development plan, later we call it as RPJMN, 2020-2024. As forest tenure reform is important as an enabling condition for the development in the forestry sector, thus the forest tenure reform should be included as national project priority in RPJMN 2020-2024.